Preparation of green-protected bamboo with excellent color fastness using natural sodium copper chlorophyll. (15th October 2022) - Qin, Meng; Wang, Zhangheng; Sun, Delin; Jiang, Xiawang; Yao, Linghua; Yu, Minggong
Abstract: Newly harvested Moso bamboo ( Phyllostachys pubescens Mazel ) was treated with sodium copper chlorophyll (SCC) for green retention using sodium chloride (NaCl) as a penetrator and sodium dodecyl benzene sulfonate (SDBS) as a surfactant. The green preservation process was optimized using the response surface methodology design, and the chemical structure, biodegradability, light resistance, and thermal stability of the green-protected bamboo were characterized. The results show that the finest green retention effect of bamboo was achieved when the period was 90 min, the temperature 90 °C, and the concentration of green retention agent 3%. Moreover, the structure and property analysis show that the SCC penetrates into the bamboo's interior through the thin-walled cells and fibers located on the surface as well as the internal pits, fills the cell cavities and cell interstices, and combines with the internal active functional groups to form hydrogen and chemical bonding. Thus it improves the light and thermal stability of bamboo effectively. Compared with original bamboo as well as bamboo prepared using traditional green preservation methods, the color stability of green-protected bamboo is preferable, and the green color maintainable for more than two years. Furthermore, biodegradation might occur, realizing the whole life cycle of green preservation of bamboo products. Highlights: Sodium copper chlorophyllin is extracted from plants, which is harmless and easy to degrade. Fresh bamboo treated with the green-keeping agent has good color fastness and light resistance. Green-protected bamboo can be biodegradable to achieve a whole life cycle green and pollution-free.